Predictive Maintenance Analytics and Fleet Downtime Reduction in U.S. Car Rental Operations (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Fleet predictive maintenance analytics are reshaping vehicle maintenance management in U.S. car rental operations, enabling operators to predict component failures before they cause downtime. The independent variable in this analysis is predictive maintenance analytics adoption, defined as the deployment of IoT sensors, machine learning models, real-time alert systems, and explainable AI output interfaces across rental vehicle fleets. The dependent variable is fleet downtime reduction outcomes, operationalized as reductions in unplanned vehicle downtime, maintenance costs, safety incidents, and customer service failures attributable to vehicle mechanical failures. Drawing on Human Capital Theory and the Technology-Organization-Environment framework, the paper conducts a systematic narrative literature review across machine learning, vehicle maintenance, fleet management, cybersecurity, and operations management. It reviews ML and explainable AI techniques for vehicle fleet maintenance prediction, maps predictive maintenance demands by vehicle system, evaluates adoption barriers including cybersecurity and data privacy risks using the TOE framework, and proposes a four-stage implementation framework with verified cost ranges and ROI measurement approaches. The paper's principal finding is that barriers to effective predictive maintenance are concentrated in the organizational dimension: sensor infrastructure is increasingly available and ML models are deployable, but the capability of operations staff to interpret, evaluate, and act on predictive alerts is not being developed systematically. Braking and tire systems carry safety and legal compliance dimensions that make human oversight a regulatory requirement as well as an operational one. The paper contributes an integrated predictive maintenance framework specific to car rental fleet operations, the first vehicle system risk matrix calibrated to rental fleet oversight demands, a TOE-grounded barrier analysis incorporating cybersecurity risks, a four-stage implementation model with ROI measurement approach, and a proposed empirical validation design for primary data confirmation.